PENYULUHAN PENCEGAHAN STUNTING PADA IBU DENGAN BALITA DI PUSKESMAS KUTA MALAKA ACEH BESAR - Muharrina, Cut Rahmi; Susanti, Ita; Nurlaila; Amalia, Shinta; Zulbaini, Angela; Maulida; Ridha, Sri Eva (Transpublika Publisher, 2020)
Reducing the prevalence of stunting in children under five is the main agenda of the Government of Indonesia. The Secretariat of the Vice President coordinates efforts to accelerate stunting prevention so that it converges, both in planning, implementation, including monitoring and evaluation at various levels of government, including villages. The Setwapres encourages the involvement of all parties in accelerating stunting prevention so that the prevalence will fall to 14% by 2024. Stunting is caused by multi-dimensional factors and is not only caused by poor nutrition experienced by pregnant women and children under five. Several factors that influence the incidence of stunting include maternal factors, home environment factors, low food quality, inadequate feeding, food and drink safety, breastfeeding (breastfeeding phase), infection, political economy, health and health services, education, social and culture, agriculture and food systems, water, sanitation and the environment. The prevalence of stunting in Indonesia is higher than other countries in Southeast Asia, such as Myanmar at 35%, Vietnam at 23%, and Thailand at 16%. Seeing this situation, of course, very worrying for the younger generation. This is because the incidence of stunting will have an impact on the growth and development of children in the long term. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of stunting, which was in the good category as much as 19 (52.8%). In conclusion, there is a significant increase in respondents' knowledge after being given counseling.